CMEA’s International Investment Bank and the crisis of developed socialism - Stone, David R. (My University, 2012)
In 1971 the Soviet bloc's Council for Mutual Economic Assistance (CMEA) created the International Investment Bank (IIB). The IIB was part of a broader effort to adopt market-based reforms in all the East-bloc economies. The bank was designed to promote competition for loans and rigorous vetting of projects, ostensibly resulting in greater CMEA integration and production that met world standards of quality. But this scenario ultimately did not pan out. Instead, the IIB became a mere conduit for Western finance, focusing not on high technology but on natural resource extraction, particularly the construction of the Soyuz natural gas pipeline. More fundamentally, the IIB could not function properly without market-determined prices and convertible currencies. Although economic authorities in the Soviet bloc fully recognized the constraints on the IIB, they were unwilling to abandon fundamental principles of the Soviet economic system.
Keywords: International Investment Bank; Council for Mutual Economic Assistance (CMEA); Socialism; Soviet Union; Multilateral economic interactions